2010
DOI: 10.1007/s10529-010-0227-7
|View full text |Cite
|
Sign up to set email alerts
|

High-level expression of functional recombinant human coagulation factor VII in insect cells

Abstract: Recombinant coagulation factor VII (FVII) is used as a potential therapeutic intervention in hemophilia patients who produce antibodies against the coagulation factors. Mammalian cell lines provide low levels of expression, however, the Spodoptera frugiperda Sf9 cell line and baculovirus expression system are powerful systems for high-level expression of recombinant proteins, but due to the lack of endogenous vitamin K-dependent carboxylase, expression of functional FVII using this system is impossible. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…We intend to analyze the expressed proteins by matrixassisted laser desorption ionization-time-of-flight spectroscopy to determine the levels of gammacarboxylation. Bioactive recombinant FVII was expressed in HEK293 cells-which endogenously express human GGCX-by co-transfecting rat Vkorc1 (Wajih et al 2008); it was also expressed in Sf9 cells (another insect cell line) by co-transfecting human GGCX (Masroori et al 2010). Mammalian cells are used to express bioactive vit.K-dependent proteins as therapeutic compounds, including recombinant FVII (Novo Nordisk, Princeton, NJ, USA), recombinant FIX (CSL Behring, King of Prussia, PA, USA), and recombinant activated protein C (Eli Lilly and Company, Indianapolis, IN, USA).…”
Section: Discussionmentioning
confidence: 99%
“…We intend to analyze the expressed proteins by matrixassisted laser desorption ionization-time-of-flight spectroscopy to determine the levels of gammacarboxylation. Bioactive recombinant FVII was expressed in HEK293 cells-which endogenously express human GGCX-by co-transfecting rat Vkorc1 (Wajih et al 2008); it was also expressed in Sf9 cells (another insect cell line) by co-transfecting human GGCX (Masroori et al 2010). Mammalian cells are used to express bioactive vit.K-dependent proteins as therapeutic compounds, including recombinant FVII (Novo Nordisk, Princeton, NJ, USA), recombinant FIX (CSL Behring, King of Prussia, PA, USA), and recombinant activated protein C (Eli Lilly and Company, Indianapolis, IN, USA).…”
Section: Discussionmentioning
confidence: 99%
“…The optimal combination of culture and feed media resulted in 20 mg/L of rFVII expression in CHO cells, a result that is higher than previously reported studies. 2,4,5,23 Moreover, it has been reported that the cell cycles phase, specifically the percentage of cells in the G0/G1 phase, significantly influences the specific productivity and production of recombinant proteins in CHO cells. [16][17][18][19] Many researchers have focused on screening for chemicals that pause the cells in the G0/ G1 phase to enhance protein specific productivity in CHO cells.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, several recombinant protein expression systems, such as Chinese hamster ovary (CHO), HEK 293 and insects cells, have been developed to express rFVII. [2][3][4][5] Moreover, Hwang et al reported using transgenic fish as bioreactors to express rFVII. 6 However, the main problem with rFVII production is its low expression level during culture.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, BHK cells and subsequently the variety of recombinant protein expression systems such as insect and other mammalian cells have been developed as a resource of FVII gene expression [4, 10, 11]. However, in this study, leishmania expression system was used as a host cell.…”
Section: Discussionmentioning
confidence: 99%